Manoeuvring at the margins : constraints faced by small states in international trade negotiations - Jones, Emily (Commonwealth Secretariat LondonGB, 2010)
Identifies the constraints that prevent small states from maximising their potential influence in trade negotiations. Analyzes the views of representatives of diverse small states on the constraints they face in negotiations.